Therapeutic Expedition of Luteolin against Brain-related Disorders: An Updated Review - Singh, Niraj Kumar; Bhushan, Bharat; Singh, Pranjul; Sahu, Kantrol Kumar (Combinatorial Chemistry & High Throughput Screening, 2025)
Brain-related disorders include neuroinflammation, neurodegenerative disorders, and demyelination, which ultimately affect the quality of life of patients. Currently, brain-related disorders represent the most challenging health problem worldwide due to complex pathogenesis and limited availability of drugs for their management. Further, the available pharmacotherapy accompanies serious side effects, therefore, much attention has been directed toward the development of alternative therapy derived from natural sources to treat such disorders. Recently, flavonoids, natural phytochemicals, have been reported as a treatment option for preventing brain aging and disorders related to this. Among these flavonoids, dietary luteolin, a flavone, is found in many plant products such as broccoli, chamomile tea, and honeysuckle bloom having several pharmacological properties including neuroprotective activities. Therefore, the objective of this paper is to compile the available literature regarding the neuroprotective potential of luteolin and its mechanism of action. Luteolin exerts notable anti-inflammatory, antioxidant, and anti-apoptotic activity suggesting its therapeutic efficacy in different neurological disorders. Numerous in-vivo and in-vitro experiments have revealed that luteolin exhibits neuroprotective potential via up-regulating the ER/ERK, PI3AKT, Nrf2 pathways and down-regulating the MAPK/JAK2STAT and NFκB pathways. Taking into account of available facts regarding the neuroprotective efficacy of luteolin, the current study highlights the beneficial effects of luteolin for the prevention, management, and treatment of different neurological disorders. Thus, luteolin can be considered an alternative for the development of new pharmacophores against various brain-related disorders.
Keywords: flavonoids